A Possibility or Just a Wish? Assessing Current Perceptions on the Potentials of a Full Student Loan Debt Forgiveness Legislation - Mbah, Ruth Endam (Advances in Social Sciences Research Journal, 2021)
Burdensome and unmanageable is what student loan repayment has become to almost 45 million Americans who owe a total of about $1.7 trillion in student loans. It is therefore intriguing to find out if a complete student loan debt forgiveness miracle is a possibility or just a wish, based on current perceptions. This study is based on the Three-Policy Window Stream Theory and the Interest Group Theory. Four mini-focus interview groups were created and their responses were analyzed using the Grounded-Theory Technique. From our findings, it is evident that student loan debt affects the mass, forming a rapidly growing informal interest group made up of mostly millennials. Yet, the pressure from this fast-growing informal interest group is not strong enough to oppose that of other interest groups like Republicans, taxpayers, financial institutions, and other stakeholders involved in student loans, to necessitate an immediate passage of legislation on student loans debt forgiveness.